Scaling behavior of dynamic hysteresis in PZT-based ferroelectric bulk ceramics - Rattikorn Yimnirun (2018)
The scaling relations for the hysteresis loops of soft and hard PZT bulk ceramics were obtained in the forms of ∝ f-0.25E0and 〈 A 〉 ∝ f-0.28E00.89, respectively, while those for the minor loops took the forms of 〈 A 〉 ∝ f-1/3E03and 〈 A 〉 ∝ f-0.43E03.19. The similarity of the scaling relations suggested that the scaling behaviors of the two types of bulk ceramics were in the same universality class and that the complex defects contributed only slightly to the dynamic behaviors. Finally, this study implied that the domain structures played significant role in controlling dynamic hysteresis behavior of ferroelectric materials. © 2008 World Scientific Publishing Company.